Molecular docking analysis of natural unusual triterpenoids towards PAK1 protein - Arslan, Idris (International Conference on Applied Engineering and Natural Sciences, 2023)
Triterpenoids are secondary metabolites produced by different natural sources and present in natural sources in the form of free acid or aglycones for triterpenoid saponins in nature. Stellettin B, rhabdaprovidine B, and neviotine A are unusual triterpenoids with their unique skeletal backbone. The serine/threonine p21-activating PAK kinases which play an important pivotal role in intracellular signaling pathways as mediator and join the biochemical process in a cell, such as cytoskeleton dynamics, in cell adhesion, polarity, motility, migration, proliferation, apoptosis, cell division, and in vesicle-mediated transport processes. In this study, molecular docking technique was used for detecting free binding of energy and inhibition constant values of selected triterpenoids towards PAK1 protein. Results showed that that ligand 1 (stellettin B) significantly inhibited the PAK1 enzyme at the value of -8.69 kcal/mol.